Ottawa gathering for the National Conference of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series - Albinati, Chris; Bonin-Labelle, Geneviève; Buddle, Kathleen; Gagnon, John; King, Gretchen (Université d'Ottawa | University of Ottawa, 2017)
National conference of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence held in Ottawa, ON 15-17 June 2017. The Canadian Radio-television and Telecommunications Commission (CRTC), according to its Three-Year Plan 2017-2020, will review the Native Broadcasting Policy (CRTC 1990-89) next year. The gatherings entitled "The Future of First Nations, Inuit and Métis Broadcasting" aim to bring practitioners, policy makers and academics together as allies to prepare a context for respectful and meaningful consultation. The idea is to create or identify the terms of reference for the CRTC deliberations to ensure that any policy changes support the development goals that Indigenous media activists, broadcasters, and community members themselves identify. This gathering seeks to share decision making power with the people, and to assert Indigenous rights to media democracy 'for as long as the waters flow'.
Keywords: First Nations; Inuit; Métis; Broadcasting; Radio; Media; CRTC; policy; Ottawa